Dynamic power-based temporary frequency support scheme for a wind farm - Jiahan You; Dan Xu; Jiangdong Cao (Frontiers in Energy Research, 2022)
Doubly fed induction generators can participate in frequency support following a disturbance by releasing their rotational energies. However, when regaining the rotor speed, a secondary frequency dip (SFD) tends to produce a sudden output drop. This study suggests a dynamic power-based stepwise inertial control (IC) scheme of a wind power plant for minimizing the SFD while reducing the maximum frequency deviation (MFD), considering the non-negligible wake. To this end, the reference of the output power increases to the torque limit. Afterward, the power reference smoothly decays with the dynamically decreasing incremental power and then automatically switches to the maximum power point tracking operation. The performance of the temporary frequency support with the suggested stepwise IC strategy is investigated with various penetration levels of wind power. Test results demonstrate that the suggested stepwise IC strategy can minimize the SFD and reduce mechanical stresses on the wind turbine during the recovery of the rotor speed while reducing the MFD. Therefore, the suggested stepwise IC strategy secures the dynamic frequency stability of an electric power system dominated by wind power generations.